Survey Kelayakan Kota Jayapura Sebagai Kota Layak Aktivitas Fisik - Kurdi, Kurdi; Ibrahim, Ibrahim; Kardi, Ipa Sari; Nopiyanto, Yahya Eko (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
The purpose of this study was to conduct a feasibility survey of the city of Jayapura as a city suitable for physical activity. So to meet these requirements, it is necessary to conduct a feasibility survey based on parameters that are protection, comfort, and feasibility that can be enjoyed by users. This research is a survey research using a qualitative approach. The qualitative research aims to understand how the results of the physical development of the city of Jayapura support the feasibility of physical activity. The research instruments include: Observation Sheets, and Documentation Sheets. The source of the research data is the researcher's documentation when conducting a survey at the location of the former implementation of PON XX Papua and public open areas in the city of Jayapura. This qualitative data analysis technique uses an analysis model of three stages, namely: data reduction, data presentation, and drawing conclusions/verification. The results of this study are 53.3% at 15 venues of PON XX Papua in Jayapura city meet the security requirements. 71.2% at 15 venues for PON XX Papua, Jayapura city, met the comfort requirements, 70% in 15 venues of PON XX Papua, Jayapura city, met the feasibility of a pleasant impression. Keywords: Survey, Appropriateness, Kota Jayapu, as a city, Physical Activity.